A multinational survey of patient utilization of and value conveyed through virtual symptom triage and healthcare referral - Gellert, George A.; Orzechowski, Piotr M.; Price, Tim; Kabat-Karabon, Aleksandra; Jaszczak, Jakub; Marcjasz, Natalia; Mlodawska, Agata; Kwiecien, Aleksandra K.; Kurkiewicz, Piotr (Frontiers in Public Health, 2023)
Objective: To describe the use patterns, impact and derived patient-user value of a mobile web-based virtual triage/symptom checker. Methods: Online survey of 2113 web-based patient-users of a virtual triage/symptom checker was completed over an eight-week period. Questions focused on triage and care objectives, pre- and post-triage care intent, frequency of use, value derived and satisfaction with virtual triage. Responses were analyzed and stratified to characterize patient-user pre-triage and post-triage intent relative to triage engine output. Results: Seventy-eight percent of virtual triage users were female, and 37% were 18-24 years old or younger, 28% were 25 to 44, 16% were 45 to 54, and 19% were 55 years or older; 41.2% completed the survey from the U.S., 12.5% from the U.K., 9.1% from Canada, 5.6% from India, 3.8% from South Africa. Motivations were to determine need to consult a physician (44.2%), to secure medical advice without visiting a physician (21.0%), and to confirm a diagnosis received (14.2%). Forty-three percent were first time users of virtual triage, 36.6% utilized a triage engine at least once every few months or more often. Pre-triage, 40.5% did not know what level of healthcare they were planning to utilize, 33.9% stated they intended to seek a physician consultation, 23.7% engage self-care and 1.8% seek emergency care. Virtual triage recommended 56.8% of patient-users consult a physician, 33.8% seek emergency care and 9.4% engage self-care. In three-fourths, virtual triage helped users decide level of care to pursue. Among 74.1%, triage recommended care different than pre-triage intentions. Post-triage, those who remained uncertain of their care path decreased by 25.4%. Patient-user experience and satisfaction with virtual triage was high, with 80.1% % stating that they were highly likely or likely to use it again, and willingness/interest in using telemedicine doubled. Conclusions: Virtual triage successfully redirected patient-users who initially planned to seek an inappropriate level of care acuity, reduced patient uncertainty of care path, and doubled the percentage of patients amenable to telemedicine and virtual health engagement. Patient-users were highly satisfied with virtual triage and the triage patient experience, and a large majority will use triage recurrently in the future.